Analisa Ekonomi Usaha Pembenihan Kerapu Cantang (Epinephelus sp.) di BBRBLPP Gondol Indonesia - Muh. Sulaiman Dadiono; Maheno Sri Widodo; Rima Oktavia Kusuma (PT. Gyandharma Global Media, 2025)
This study presents an economic analysis of the cantang grouper (Epinephelus sp.) the hatchery at the BBRBLPP Gondol. The research objective is to provide information to business actors in developing the grouper hatchery sector in Indonesia. The results of the business analysis show that the investment costs needed for the cantang grouper hatchery business activities are Rp. 336,590,000. depreciation of Rp. 35,615,000. The fixed cost required for one year is Rp. 164,615,000. Production costs to be incurred in the amount of Rp. 176,299,000. Revenue obtained for one year is Rp. 345,600,000. The profit gained during the year is Rp. 169,301,000. An R/C ratio of 1.96 means that each additional cost of Rp. 1 will receive an income of Rp. 1.96. Payback Period of 1,988, meaning the investment costs incurred will be returned after the hatchery business runs for 2 years. BEP rupiah of 171,473,958. This means that the turning point will be reached if the seed sales reach IDR 171,473,958. BEP unit of 28,396, which means the turning point of hatchery venture capital will be achieved if seed production reaches 28,396. The prospect of Cantang grouper hatchery business in the future is up-and-coming for the Bali region. Most grouper farmers prefer the cantang grouper because the development of the cantang grouper is faster and more resistant to disease.